Synergetic effect of combining PEF treatments with sublethal doses of SO2 on the inactivation of Saccharomyces bayanus and Brettanomyces bruxellensis in red wine - Delso, Carlota; Berzosa, Alejandro; Sanz, Jorge; Álvarez, Ignacio; Raso, Javier (Frontiers in Food Science and Technology, 2023)
Certain microorganisms are capable of proliferating in wine despite its low pH and high ethanol content. The yeasts of the Saccharomyces genus responsible for alcoholic fermentation can alter wines with residual sugars; the proliferation of Brettanomyces bruxellensis brings about thoroughly unpleasant sensory changes. The main strategy currently applied in wineries for microbial control is the addition of sulfites (SO2). However, sulfites are being researched due to the symptoms they can cause in allergic individuals. Pulsed electric field (PEF) technology has the capability of inactivating vegetative cells of microorganisms at non-lethal temperatures and could thus prove to be an alternative to SO2. In this study, the resistance of Saccharomyces bayanus and B. bruxellensis suspended in wine to a series of different PEF treatments (10–25 kV/cm; 25–1000 µs; 40–170 kJ/kg) combined with sublethal concentrations of SO2 (10, 25, and 50 ppm) was evaluated. The results showed that even the least intense PEF treatments (10 kV/cm; 115 kJ/kg) inactivated more than 4.0 Log10 cycles in both types of yeasts immediately after treatment. The subsequent incubation of the treated yeasts for 24 h in wine managed to increase inactivation by 3.0 Log10 cycles. The combination of a moderate PEF treatment with sublethal doses of SO2 had a synergistic lethal effect on the two yeasts under study after 24 h of incubation in wine, leading to counts lying below the detection limit (>5.0 Log10 cycles). This synergistic effect was attributed to the existence of a portion of the population that had been sublethally damaged by PEF and in which SO2 could more easily penetrate the cytoplasm. These results demonstrate the capacity of PEF technology for microbial control of spoilage yeasts in wine. PEF could thus represent an alternative with the potential of eliminating or reducing SO2 levels in the winemaking process.